SYNTHESIS, CHARACTERIZATION AND APPLICATION OF NEW CROSS-LINKED AND MODIFIED POTASSIUM POLYACRYLATE AS SOIL AMENDMENTS - Majied, Zahraa Ahmed; Jabarah, Zainab A.; Al-Hassoon, Samira Nasir Hasoon (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was carried to investigated Two types of new grafted polymers were prepared through chemical blending (mixture of the crosslinked mixture polymerization) of potassium polyacrylate (KPA) and 2-amino acetic acid (glycine) with calcium nitrate to give graft polymer type-1 (KPA-g-CaGY). As well as reaction of potassium polyacrylate (KPA) with calcium nitrate and chitosan polymer to give graft polymer type-2 (KPA-g-CaCS), grafting polymers has been characterized by FT-IR, 1HNMR spectroscopy and compared with the pure potassium polyacrylate. The prepared polymers were used after confirming their diagnosis and physic-chemical properties in trying to reclaiming the desertification and saline soil in (Abu Ghraib-Baghdad in July 2023) by planting Iraqi sorghum type-70. Physical properties were test (before/after planting) by XRD of (KPA-g-CaGY) showed cross linked as crystal type-1, while KPA-g-CaCS showed cross linked as amorphous type-2 compared with KPA. In addition (SEM) Scanning Electron Microscopy of the modified polymer gave clear micrographs of the type-1 (KPA-g-CaGY) and type-2 (KPA-g-CaCS), this reinforces our claim that the polymer remains in the land after planting, after more than four months, and does not change or degradation, and enhances the use of the land for more than one season without adding the polymer to it. In addition to the equilibrium swelling percentage has been investigated in media (well water pH=8.5 and tap water pH=6.9), KPA-g-CaCS shows higher uptake of water compared with KPA and PAK-g-CaGY, suggests more hydrophilicity absorption at different times.